Until they sail [videorecording (DVD)] - Wise, Robert, 1914-2005; Simmons, Jean, 1929-2010; Fontaine, Joan, 1917-2013; Newman, Paul, 1925-2008; Laurie, Piper, 1932-; Drake, Charles, 1917-1994; Dee, Sandra; Michener, James A. (James Albert), 1907-1997 (Distributed by Warner Home Video, 2011)
The men of New Zealand march off to war, leaving behind cities and villages filled with women and loneliness. In time, new men come ashore: U.S. Marines facing uncertain futures in Pacific battles yet to come. And new loves, tender or tragic, transitory or lasting, begin to flower.